Prognostic significance of serum progranulin level in de novo adult acute lymphoblastic leukemia patients - El-Ghammaz, Amro M. S.; Azzazi, Mohamed O.; Mostafa, Nevine; Hegab, Hany M.; Mahmoud, Amir A. (Clinical and experimental medicine, 2020)
Increased expression of progranulin (PGRN) has been reported in some hematological cancers, but limited information regarding its significance in acute lymphoblastic leukemia (ALL) is available. This study involved 60 subjects (40 de novo adult ALL patients and 20 controls). Serum PGRN level was measured by enzyme-linked immunosorbent assay and was correlated with patient outcome. Serum PGRN level was significantly higher in patients than controls. Serum PGRN level did not correlate with age, total leukocytic count, hemoglobin, platelets, absolute blast count in peripheral blood, lactate dehydrogenase, percent of blasts in bone marrow, gender, comorbidities, the presence of central nervous system infiltration, ALL phenotype, cytogenetics and risk of the disease. High serum PGRN level was not associated with inferior overall survival (OS) on univariate analysis. Regarding cumulative incidence of relapse (CIR) and disease-free survival (DFS), high PGRN level was associated with poor results on univariate analysis. Moreover, it tended to be independent risk factor on multivariate analysis for CIR but was not an independent predictor of inferior DFS. Serum PGRN level is significantly elevated in de novo adult ALL patients and may be used as a predictor of increased relapse risk.